Potentiometric Performance of Ion-Selective Electrodes Based on Polyaniline and Chelating Agents: Detection of Fe2+ or Fe3+ Ions - Ismail, Rimeh; Šeděnková, Ivana; Černochová, Zulfiya; Romanenko, Iryna; Pop-Georgievski, Ognen; Hrubý, Martin; Tomšík, Elena (Biosensors, 2022)
We constructed a sensor for the determination of Fe2+ and/or Fe3+ ions that consists of a polyaniline layer as an ion-to-electron transducer; on top of it, chelating molecules are deposited (which can selectively chelate specific ions) and protected with a non-biofouling poly(2-methyl-2-oxazoline)s layer. We have shown that our potentiometric sensing layers show a rapid response to the presence of Fe2+ or Fe3+ ions, do not experience interference with other ions (such as Cu2+), and work in a biological environment in the presence of bovine serum albumin (as a model serum protein). The sensing layers detect iron ions in the concentration range from 5 nM to 50 µM.
Keywords: chelátory; Electrodes; Ions; Aniline Compounds; poly(2-methyl-2-oxazoline)s; aniliny; iontově selektivní elektrody; Ion-Selective Electrodes; koncentrace vodíkových iontů; Chelating Agents; sensor of Fe2+ or Fe3+ ions; potentiometry; ionty; Hydrogen-Ion Concentration; analysis; non-biofouling layer; elektrody